Older people in emergencies : considerations for action and policy development - Hutton, David (World Health Organization, 2008)
Older people have often been overlooked in disasters and conflicts, and their concerns have rarely been addressed by emergency programs or planners. This analysis seeks to highlight factors that particularly affect older people in emergencies, especially health-related concerns, propose a strategy to raise awareness about older people in emergencies and recommend policies and practices to address these considerations.--Publisher's description.